Epidermal hydration levels in patients with rosacea improve after minocycline therapy. (5th June 2014) - Ní Raghallaigh, S.; Powell, F.C.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Patients with rosacea have features suggestive of abnormal skin barrier function. Sebum, pH and hydration levels influence this epidermal homeostasis. The activity of the epidermal protease enzyme kallikrein 5 is increased in rosacea. Protease enzymes are most active at an alkaline pH. What does this study add? Patients with papulopustular rosacea (PPR) have normal sebum casual levels, reduced epidermal hydration levels and a more alkaline centrofacial pH compared with control subjects. Hydration levels in patients with PPR increase after minocycline treatment, while skin pH and sebum levels remain unchanged.